Contextual Socio-Ecological Types in Kesra - Shiri, Zahra; Le, Quang Bao; Frija, Aymen; Rejeb, Hichem (International Center for Agricultural Research in the Dry Areas, 2023)
The impact of agricultural activities on the environment and its less favorable consequences on resources such as land support and water resources are more harmful in mountainous areas than in the plains since mountain agriculture has specific characteristics: difficult natural environment related to altitude and climate, fragility of natural resources and land resources, the sharp decline in the number of farms due to social and geographical isolation. The management of natural resources or the farm management at the local level in the mountainous areas need a deep and specific analysis to study the social system (users, managers and governance institutions using technologies and infrastructures) who manage artificial and natural resources. Analyzing socio-ecological context allow encompassing the complexity of the social, ecological, and socio-ecological interactions. Hence becomes the necessity to understand the global landscape through different types of socio-ecological context. Understanding these types is important for developing effective strategies for sustainable development, conservation, and adaptation to environmental changes. This Poster occurred during the 20th International Scientific Day of INRGREF in Tunis, Tunisia “Sustainable Ecosystem Management for Agroecological Transition and Food Security” (10-11 October 2023).